ANALISIS KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS INDUSTRI KECIL GULA AREN DI DESA CAMPOAN KECAMATAN MLANDINGAN - Iksan Hadi; Ahmad Hafas Rasyidi; Ida Fitriana Ambarsari (LPPM Politeknik Pratama, 2025)
The development of small enterprises requires businesses to compete by offering quality products at appropriate prices. This study aims to analyze the effect of product quality and price on purchasing decisions of palm sugar in Campoan Village, Mlandingan. A quantitative approach was employed with simple random sampling involving 100 respondents. Data were analyzed using multiple linear regression. The results indicate that product quality has a positive and significant effect on purchasing decisions, while price shows no significant effect. Simultaneously, product quality and price influence purchasing decisions, with product quality being the dominant factor. These findings highlight that improving product quality is the key strategy to strengthen consumer purchasing decisions.